Pengaruh Motivasi dan Disiplin Kerja Terhadap Kinerja Mahasiswa/Mahasiswi Karyawan di Daerah Legok - Alfiqri Zainudi; Dwi Muhammad Refo; Ade Putra Ferdiansyah (Yayasan Literasi Sains Indonesia, 2022)
Motivating employees to improve employee performance is so optimal that it is necessary in every company so that employees feel cared for by management, so motivation for performance is so good and according to company targets. This study aims to determine the effect of work motivation and work discipline on the performance of students who are in the area Legok partially, and to determine the effect of work motivation and work discipline on the performance of students simultaneously. The type of research used is explanatory research with a quantitative approach. The sample used was 102 respondents where the data collection technique in this study used a questionnaire or questionnaire which was distributed to student employees in the Legok area. The data analysis technique uses multiple linear tests, t test, f test, coefficient of determination test with the help of SPSS 24. Based on the results of the study it shows that work motivation partially does not have a significant effect on the performance of student employees in the Legok area. However, the test results show that work discipline affects the performance of student employees in the Legok area. Work Motivation and Work Discipline simultaneously have a significant effect on the performance of student employees in the Legok area with a presentation of 65%.